Characteristics and Management of Neck and Trochanteric Femur Fractures at a Tertiary Hospital in Indonesia: A Retrospective, Single-Center Study - Pulungan, Ndilalah; Thoriq, Yusa Muhammad; Hartono, Felix Giovanni; Adnan, Muhammad Luthfi; Sasetyo, Dadang Rona (Universitas Airlangga, 2024)
Background: Although hip fractures are common among the elderly population, there are still limited studies on neck-trochanteric fractures, one of the less common types of hip fractures. This study aims to describe the characteristics of patients and their management in patients with neck trochanteric fractures. Methods: This retrospective cross-sectional study analyzed medical records of patients aged >18 years with trochanteric fractures from a tertiary hospital in Central Java, Indonesia, between January and December 2021. Fracture types were identified and classified using the Garden, Pauwels, and AO/OTA classifications. Demographic data, risk factors, fracture locations, and treatment types were also collected. Statistical analysis was performed using SPSS 21.0 to describe patient characteristics. Results: The total sample was 77 patients, most were female (n = 55 (71.4%)) and aged > 60 years. More than a third of diagnosed fractures were neck of the femur fractures in 33 patients (42.9%). Among the most common classification types of fractures were Garden Type 3, Pauwels Type 3, and AO/OTA type A1.1. A total of 33 patients (42.9%) underwent open reduction of the fracture with internal fixation. Conclusions: Our findings show that the prevalence of neck-trochanteric fractures mostly occurs in patients > 60 years of age and in females. Although open reduction with internal fixation is generally performed, there are several cases of fractures that are not classifiable due to limited imaging examinations. Further research on a wider population is needed to confirm the findings of this study.